2007
DOI: 10.1007/s00018-007-7080-4
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiglioma action of metformin: cell cycle arrest and mitochondria-dependent apoptosis

Abstract: The present study reports for the first time a dual antiglioma effect of the well-known antidiabetic drug metformin. In low-density cultures of the C6 rat glioma cell line, metformin blocked the cell cycle progression in G(0)/G(1) phase without inducing significant cell death. In confluent C6 cultures, on the other hand, metformin caused massive induction of caspase-dependent apoptosis associated with c-Jun N-terminal kinase (JNK) activation, mitochondrial depolarization and oxidative stress. Metformin-trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
161
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(175 citation statements)
references
References 44 publications
10
161
1
3
Order By: Relevance
“…It has been previously demonstrated that the action of metformin is temperature-dependent [5]. We also observed that high concentrations of metformin impair the oxidative phosphorylation system (Table 1), that is in accordance with a previous study demonstrating that metformin causes mitochondrial depolarization [10].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been previously demonstrated that the action of metformin is temperature-dependent [5]. We also observed that high concentrations of metformin impair the oxidative phosphorylation system (Table 1), that is in accordance with a previous study demonstrating that metformin causes mitochondrial depolarization [10].…”
Section: Discussionsupporting
confidence: 93%
“…However, it has also been shown that metformin prevents the mitochondrial permeability transition pore (PTP) opening in both permeabilized and intact KB cells [8], and in permeabilized human microvascular endothelial cells (HMEC-1) [9]. In opposition, Isakovic et al [10] reported that metformin acts as a PTP inducer in C6 rat glioma cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, metformin has been documented to prevent cell death by modulation of the mitochondrial permeability transition pore opening induced by a glutathione-oxidising agent t-butyl hydroperoxide (Guigas et al 2004) and also due to high glucose-induced cell death in a human dermal microvascular endothelial cell line, HMEC-1 (Detaille et al 2005). However, reports of metformin treatment resulting in an increase in H 2 O 2 production in rat liver mitochondria (Carvalho et al 2008), a short-term trial involving 15 type 2 diabetes mellitus patients treated with metformin showing an elevation in oxidative stress, indicated by elevated malidialdehyde levels (Škrha et al 2007) and metformin causing mitochondrial depolarization and oxidative stressdependent apoptosis in cultured glioma cells (Isakovic et al 2007), suggest that the role of mitochondria in metformininduced cytotoxicity remains to be of defined.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin has also been reported to increase H 2 O 2 production in rat liver mitochondria and exacerbated Ca 2+ -induced mitochondrial permeability pore opening in a concentration-dependent manner (Carvalho et al 2008). Moreover, metformin in cultured glioma cells has been shown to cause mitochondrial depolarization and oxidative stress-dependent apoptosis (Isakovic et al 2007). Collectively, these observations suggest that a key cellular effect of metformin could be the general impairment of mitochondrial bioenergetic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin may have direct effects on cancer cells through the activation of AMP-activated protein-kinase (AMPK). Furthermore, it is able to inhibit mammalian target of rapamycin complex 1 (mTORC1), a down-stream effector of AMPK and is expected to decrease oncogenic proliferation in some cancers (Dowling et al, 2007;Isakovic et al, 2007;Jiang et al, 2008;Zakikhani et al, 2006).…”
Section: Introductionmentioning
confidence: 99%